Utilization of Geographic Information Systems for 1999 Election Results Mapping in Yogyakarta Special Province - Endang Saraswati (Forum Geografi, 1999)
Up to present data and information relating to result of general eletion, 1999 still in tabuler for especially in form of figures. Data presentation in form of tables has disadvantage such as not attractive as well as not so effective for communication. Data presentation which is able to adapt the demand is presented in form in map. The aims of this research are 1) to depict data of general election result, in 1999 in form on digital map; 2) to identify factors which influence the result of vote, using map analysis technique of resulted map. The methodology of the research is to use secondary data, mean while the methods for its mapping to apply point symbol, line, and area which appropriated with data characteristics and expected visual perception of the data. The data then is elaborated with aid of Geographic Information System (GIS), to produce map of vote result in general election 1999. To identify what factors that influence voice between map of vote result and map  of population amount, according to education, occupation, and religion.The result of the research show that Partai Demokrasi Indonesia Perjuangan got highest voices, that is 33,73% followed by Partai Amanat Nasional 15,87%, Partai Golongan Karya 13,78%, Partai Kebangkitan Bangsa 13,43%, Partai Persatuan Pembangunan 4,95% and the rest 18,20% for 43 other parties. The voice gathering to occupation and their religion. The voice which are gathered by Partai Demokrasi Indonesia Perjuangan ome from middle to lower group of society which are nasionalist interest, either live in urban area or in rural area. Participant of Partai Amanat Nasional come from modern moslem group and member of Muhammadiyah, result in the voice of Partai Amanat Nasional is high in urban area. The voice which is gathered by Golongan Karya for urban area come from group of birocrate consists of official/ military/ pension, meanwhile form rural area come farmers who enjoy product result of new era regime, especially in agriculture sector. Partai Kebangkitan Bangsa gathered the voicein rural area with Nadhatul Ulama infrastructure and traditional organization which is solid strong under leading of Kyai.